2017
DOI: 10.1177/0271678x17700435
|View full text |Cite
|
Sign up to set email alerts
|

Dementia incidence and predictors in cerebral amyloid angiopathy patients without intracerebral hemorrhage

Abstract: Cerebral amyloid angiopathy (CAA) is a common cause of cognitive impairment in older individuals. This study aimed to investigate predictors of dementia in CAA patients without intracerebral hemorrhage (ICH). A total of 158 non-demented patients from the Stroke Service or the Memory Clinic who met the modified Boston Criteria for probable CAA were included. At baseline, neuroimaging markers, including lobar microbleeds (cerebral microbleeds (CMBs)), white matter hyperintensities (WMH), cortical superficial sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 40 publications
2
41
1
Order By: Relevance
“…Thirteen articles met the aforementioned criteria ( Fig. 1) [16][17][18][19][20][21][22][23][24][25][26][27][28]. Three studies analyzed longitudinal data [16,17,19] and ten were cross-sectional studies [18,[20][21][22][23][24][25][26][27][28].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirteen articles met the aforementioned criteria ( Fig. 1) [16][17][18][19][20][21][22][23][24][25][26][27][28]. Three studies analyzed longitudinal data [16,17,19] and ten were cross-sectional studies [18,[20][21][22][23][24][25][26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…The follow-up time ranged from 2.3 years (median) to 5.2 years (mean). Two studies reported the number of cases of all-cause dementia [17,19], whereas one study specified the subtypes, i.e., AD and VaD [16]. Two studies examined the general population and one study examined subjects with probable CAA.…”
Section: Study Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both DPA and CAA are the major sources of VCI and vascular dementia , with a cumulative dementia incidence of around 70% after 5 years for CAA patients . Around one of three of the DPA and CAA subjects seem to reveal VCI, with disturbed executive function and reduced processing speed as well as CAA‐related visuoperceptual impairment being the most consistent findings .…”
Section: Neuroimaging Biomarkers Of Sporadic Csvdmentioning
confidence: 86%